Anti-apoptotic effect of HeidihuangWan in renal tubular epithelial cells via PI3K/Akt/mTOR signaling pathway. (10th February 2023) - Li, Ying-Ying; Tian, Zeng-Hui; Su, Shan-Shan; Shi, Jing-Jing; Zhou, Chao; Zhang, Li-Hua; Zhang, Fa-Rong; Hao, Yan-Ke
Abstract: Ethnopharmacological relevance: Heidihuang Wan (HDHW) is a classic Chinese herbal formula, which was first recorded in the "Suwen Bingji Qiyi Baoming Collection" written by Liu Wansu during the Jin Dynasty (1115-1234 AD). It is commonly used clinically for the treatment of kidney diseases and its curative effect is stable. Previous animal experiments have confirmed that HDHW can effectively improve renal fibrosis. However, the underlying pharmacological mechanism remains unclear. Aims of this study: Renal tubular epithelial cell (RTEC) apoptosis is one of the main pathological features of renal fibrosis. This study aimed to observe the effect and underlying mechanism of HDHW on the apoptosis of RTECs to further explore the pathological mechanism of HDHW against renal fibrosis. Materials and methods: We examined the HDHW composition in rat serum. In vitro, we first screened out the optimal intervention concentration of HDHW on RTECs using the MTT assay. Hypoxia/reoxygenation was then used to induce apoptosis of RTECs (H/R-RTECs), which were divided into H/R-RTEC, astragaloside IV (positive control), HDHW, and RTECs groups. After 48 h of drug intervention, apoptosis of RTECs was detected using flow cytometry and protein expression was detected by western blotting. The 5/6 nephrectomy rat model was constructed and divided into the normal control, 5/6 nephrectomy, HDHW, and astragaloside IV groups. After 8 weeks of treatment, TUNEL staining was used to detect cell apoptosis, and western blotting was used to detect protein expression. Results: HDHW downregulated the expression of pro-apoptotic proteins Bax and Caspase3, up-regulated the expression of anti-apoptotic protein Bcl-2, activated the PI3K/Akt/mTOR signaling pathway, and reversed the early apoptosis of RTECs, thereby resisting the apoptosis of RTECs. Conclusion: HDHW inhibits apoptosis of RTECs by modulating the PI3K/Akt/mTOR signaling pathway. This study provides experimental evidence for the anti-fibrotic effect of HDHW on the kidneys and partially elucidates its pharmacological mechanism of action. Graphical abstract: Image 1 Highlights: HDHW inhibits the apoptosis of renal tubular epithelial cells in vitro. HDHW inhibits apoptosis of RTECs accompanied by activation of PI3K/Akt/mTOR. Inhibition of RTECs apoptosis is the mechanism of HDHW against renal fibrosis. This study provides a new idea for the treatment of renal fibrosis.